Experiencing and responding to climate change in the Andes - Wauben, Noortje (2020)
Climate change poses a significant challenge to society, in particular as it constitutes a threat to food security. Considering Andean campesinos are heavily affected by changes in the climate and substantially contribute to the food security of the larger Andean population, it is crucial to investigate their experiences with – and (undertaken and proposed) responses to – changes in the climate. The objective of this research is to investigate what campesinos in the Andean highlands of Southern Ecuador consider to be effective and appropriate responses to changes in the climate, and how this is influenced by perceptions, values and knowledge related to these changes. This is done by means of semi-structured interviews centered around the four axioms of perception, values, knowledge and response (as identified by Roncoli et al 2016). The study finds that reforestation (with native species), reducing contamination (of waste and toxic residues), and improving education on how to behave towards the environment are recurrently considered to be effective and appropriate responses to changes in the climate by campesinos in the highlands of Southern Ecuador. Locating the perceived changes and the known causes of changes in the climate in the immediate environment, along with values related to taking social responsibility for changes in the environment, are suggested to have contributed to the research participants largely taking on the responsibility themselves to undertake the strategies to limit future changes in the climate. The results of this research are important for a more contextualized understanding of climate change, and for the development of climate change response policies that reflect campesino needs, values and interests, and – as such – are expected to have a greater success rate of implementation due to greater local acceptance.